Thiamine Levels in Muscle and Eggs of Adult Pacific Salmon from the Fraser River, British Columbia. Issue 3 (10th July 2018) - Welch, David W.; Futia, Matthew H.; Rinchard, Jacques; Teffer, Amy K.; Miller, Kristi M.; Hinch, Scott G.; Honeyfield, Dale C.
Abstract: Multiple species and stocks of Pacific salmon Oncorhynchus spp. have experienced large declines in the number of returning adults over a wide region of the Pacific Northwest due to poor marine survival (low smolt‐to‐adult survival rates). One possible explanation for reduced survival is thiamine deficiency. Thiamine (vitamin B1 ) is an essential vitamin with an integral role in many metabolic processes, and thiamine deficiency is an important cause of salmonid mortality in the Baltic Sea and in the Laurentian Great Lakes. To assess this possibility, we (1) compared muscle thiamine content over time in a holding experiment using Fraser River (British Columbia) Sockeye Salmon O. nerka to establish whether adults that died during the holding period had lower thiamine levels than survivors, (2) measured infectious loads of multiple pathogens in held fish, and (3) measured egg thiamine content from four species of Pacific salmon collected on Fraser River spawning grounds. Chinook Salmon O. tshawytscha had the lowest egg thiamine, followed by Sockeye Salmon; however, egg thiamine concentrations were above levels known to cause overt fry mortality. Thiamine vitamers in the muscle of Fraser River adult Sockeye Salmon shifted over a 13‐d holding period, with a precipitous decline in thiamine pyrophosphate (the active form of thiamine used in enzyme reactions) in surviving fish. Survivors also carried lower loads of Flavobacterium psychrophilum than fish that died during in the holding period. Although there is no evidence of thiamine deficiency in the adults studied, questions remain about possible thiamine metabolism–fish pathogen relationships that influence survival.